STUDI DESKRIFTIP KARAKTER KEPEMIMPINAN PCM BUKATEJA DAN PCM KEJOBONG KABUPATEN PURBALINGGA - Sri Harmianto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
The condition of the organizational activity of the Persyarikatan Muhammadiyah at the branch and sub branch level in Purbalingga Regency is very diverse, since there are Muhammadiyah Branches that are advanced but less active, Muhammadiyah branches that have many active Muhammadiyah Sub Branches, and there are also less active Muhammadiyah Branches with less active Muhammadiyah Sub Branches. Interestingly, there are Muhammadiyah Branches which are less active, but have many active Muhammadiyah Sub Branches. In this study, the leadership styles of the advanced Muhammadiyah Branches were investigated, namely the Muhammadiyah Branch Leaders (PCM) Bukateja and PCM Kejobong. Furthermore, the leadership style of the advanced Muhammadiyah Branch can be a guide for the relatively passive sub branches of Muhammadiyah. From the results of the study, it was found that the most dominant types of leadership were the Chairman of the Muhammadiyah Regional Leadership (PDM), the Head of the Branch and Sub Branch Development Institute (LPCR), and the Head of the Branch, namely the charismatic leadership type, then the democratic leadership type, the leadership type that likes development, and transformational leadership type. Thus, the recommendation is the type of leadership in the Persyarikatan Muhammadiyah Purbalingga Regency needs special attention because currently it is mostly held by the